Differentiation of University Freshman in Arts and Science on the General Occupational Themes of the Strong-Campbell Interest Inventory - Meuser, Peter E.; McInnis, Charles E. (Canadian Journal of Counselling and Psychotherapy, 2012)
Occupational personality types of Arts and Science freshmen were comparedemploying the six General Occupational Themes of the Strong-Campbell Interest Inventory in a multiple-discriminant analysis. Subjects were 202 male and 158 female freshmen registered in either Arts or Science faculties at the University of Ottawa. Univariate analyses of variance between groups on all Themes indicated significant mean differences. Chi-square analyses determined eachdiscriminant-function to be significant in its differentiating power. Discriminant-and classification-function coefficients were established for each Theme, makingpossible correct classification of each individual with a greater degree of accuracy than could be expected by chance. The .01 level of probability was applied in all instances where significance was tested. Findings suggested that male Arts, male Science, female Arts, and female Science freshmen were distinctly different from each other in terms of personality types, and that indiscriminate counselling may overlook important differences.